Efeito dos níveis de triptofano digestível em dietas para codornas japonesas em postura - Pinheiro, Sandra Regina Freitas [UNESP]; Barreto, Sergio Luiz de Toledo; Albino, Luiz Fernando Teixeira; Rostagno, Horacio Santiago; Umigi, Regina Tie; Brito, Claudson Oliveira (FapUNIFESP (SciELO), 2008)
The adequate level (0.12, 0.16, 0.20, 0.24, and 0.28%) of the dietary digestible tryptophan was evaluated in 400 laying Japanese quail from 21 to 30 weeks old. The animals were housed in laying cages, with initial weight of 158.50 g and egg production average of 84.50%. A completely randomized blocks design, with eight blocks, five diets, eight replicates of ten birds per replicate and three experimental periods of 21 days each was used. Feed intake (g/bird/day), digestible tryptophan intake (mg/bird/day), egg production (%/bird/day), egg weight (g), egg mass (kg/bird/day) and feed conversion (kg feed intake per kg eggs and dozen eggs) were the characteristics evaluated. Only the characteristics digestible tryptophan intake and egg production rate show significant effects of digestible tryptophan levels in the diets. Performance response of the Japanese quails in posture, regarding the adjustment obtained through models of linear regression and broken-line regression model, and the biological interpretation, allow to conclude that to obtain the best productive performance, the Japanese quails diets should contain the level of 0.21% digestible tryptophan, that results in a daily intake of 45.0 mg/ bird of digestible tryptophan, corresponding to the digestible tryptophan: digestible lysine ratio of 21%. © 2008 Sociedade Brasileira de Zootecnia.
Dietary digestible tryptophan levels for Japanese laying quails
Keywords: Amino acids; Coturnix coturnix japonica; Requirement; Serotonin; Animalia; Aves; Coturnix; Coturnix japonica; Phasianidae